COMPARISON OF LASER SCANNING AND PHOTOGRAMMETRY AND THEIR USE FOR DIGITAL RECORDING OF CULTURAL MONUMENT CASE STUDY: BYZANTINE LAND WALLS-ISTANBUL - Bayram, B.; Nemli, G.; Ozkan, T.; Oflaz, O. E.; Kankotan, B.; Cetin, I. (INT SOC PHOTOGRAMMETRY REMOTE SENSING C/O SCHOOL OF SURVEYIN, 2015)
3D modeling of cultural monuments is very crucial issue for preparing restoration projects. However, it has challenges such as data acquisition, preparation and processing. 3D modeling of objects can be time consuming and may include some difficulties due to the complexity of the structures. 3D terrestrial laser (TLS) scanning technique is one of the reliable and advantageous methods for 3D reconstruction of monuments. This technique is commonly acknowledged due to its accuracy, speed and flexibility. But the suitability and capability of this technique depends on proper usage, and good survey planning. Magnificent developments in high-resolution digital sensor technologies leaded to manufacturing of new camera systems. Parallel to these innovations, development of computer systems and image processing techniques made enable to obtain multiple image-based 3D object models. In the presented study, TLS method has been compared to conventional photogrammetric and image-based dense matching methods. Automatic dense point creation has been realized by our developed algorithm and PIXEL-PHOTO software which generates 3D point clouds from stereo images. The reliability and encountered problems during point cloud measurement process have been discussed. The study area has been chosen as historical Byzantine Land Walls of Istanbul, which constitute a remarkable area defining the ancient city's historical peninsula.
Keywords: Cultural Heritage; Terrestrial Laser Scanning; Image matching; Photogrammetry; 3D Modeling; IMAGE-ANALYSIS; CONCRETE; Physical Geography; Remote Sensing; Imaging Science & Photographic Technology